A ciência na saúde e na doença: atuação e prática dos médicos em Fortaleza (1900-1935) - Garcia, Ana Karine Martins (2011)
This work proposes to analyze the speeches and actions concerning to doctors practices at Fortaleza city in the early twentieth century. And, specially, understand the strategies and measures employed for more active participation of this group in the city. Among the main issues examined in this work, there are: the role of the doctors in actions to improve the health, the search for a more effectively workspace in the field of public health, training and participation of the Centro Médico Cearense (Medical Center from Ceará), in Fortaleza, and the interventions of doctors from Ceara and the Rockefeller Commission in preventing and fighting yellow fever. The diversified research sources contributed to understand how doctors earned at that time a place in directing and organizing the daily life of Fortaleza (1900-1935)